Molecular characterization of Sarocladium oryzae isolates causing sheath rot in paddy (Oryza sativa) - G, VENKATAESHA M; KUMAR, ATUL; JOSHI, MONIKA A; SINGH, AMIT KUMAR; DUBEY, S C; BHAUMICK, PROLAY KUMAR (The Indian Journal of Agricultural Sciences, 2019)
Sheath rot, caused by Sarocladium oryzae (Sawada) W. Gams & D. Hawksw, is an important seed borne fungal disease of paddy (Oryza sativa L.). In the present investigation, diseased specimens were collected in kharif 2016 and 2017 from more than 55 different geographical locations spread across 15 states of the country and variability in 30 isolates of Sarocladium oryzae was studied by molecular methods. The molecular characterization using two marker systems, i.e. Inter-Simple Sequence Repeat (ISSR) and Random Amplified Polymorphic DNA (RAPD) was carried out which revealed differences in isolates collected from different geographical locations. After preliminary screening, out of 22 ISSR and 24 RAPD primers, 8 ISSR and 7 RAPD primers were used against all the isolates. Percent polymorphic ranging between 53.1–100% in ISSR and 61.4–100% in RAPD was recorded with all the isolates. The average number of bands in ISSR markers was 63.3, and 71.8 in RAPD markers. All RAPD primers showed 100% polymorphism except OPS13 (61.4%) and OPD5 (74%). Among ISSR primers ISSR5 and ISSR18 showed 100% polymorphism. Cluster analysis of individual and combined primers was done. In the combined cluster analysis of RAPD and ISSR markers, the isolates from same geographical region were in same cluster as evident from the cluster I that includes Kadapa, Ragolu, Maruteru, West Godavari and Adutharai, which are from southern plain region of the country. Similar observations were recorded when data analysis of individual marker system was carried out which revealed that the two different marker systems applied complement each other in characterizing various isolates.